PREFIXES FOUND ON SELECTED BARACK OBAMA’S INSTAGRAM CAPTION: MORPHOLOGICAL STUDY - Ida Bagus Made Sadu Gunawan; Winarta, Ida Bagus Gde Nova; Prawita, Ni Ketut Riska Dewi (Yavana Bhasha : Journal of English Language Education, 2025)
ABSTRACT The purpose of this study was to interpret and describe the prefix type from Barack Obama's Instagram caption. It is because Barack Obama have good personal in the public, such as he is win the Nobel Peace Prize and third to win a Nobel Prize while in office. The name Barack means "one who is blessed" in Swahili. Barack Obama is the first African-American to be president of the Harvard Law Review. In English Morphology, there is Prefix and Suffix. But, in this study only discuss about prefix that was used by Barack Obama in Instagram Caption. Prefix in morphology is one of affixes, generally prefix is indicated as inflectional morphemes. The writer uses descriptive qualitative method to analyze the types of the prefix by using theory from Lieber (2009). The data found was analyzed by using tree diagram. Based on the analysis the writer found some prefix, such as: re-, un-, in-, dis-, and auto-.